2015
DOI: 10.1553/eco.mont-7-1s26
|View full text |Cite
|
Sign up to set email alerts
|

Trail management, off-trail walking and visitor impact in the Pieniny Mts National Park (Polish Carpathians)

Abstract: The objective of this study was to determine the numbers and percentages of various groups of visitors hiking off trail, the motives driving visitors to do so and the damaging impact on nature and the environment. Sections of eight routes in the Pieniny Mts. National Park (NP) were selected for the study. On average, 29.4 % of visitors were found to have strayed from the official routes, with children being the most prominent group (38.2 %). The groups led by guides left the trails significantly less than othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…This result is logical and was expected given environmental factors (the attributes which describe individuals' immediate surroundings) are consistent and strong predictors of behavioral responses, even when cognitive and sociodemographic characteristics are controlled for (Gifford 2014). While a substantive amount of previous research has either suggested anecdotally or implied a relationship between degraded trail conditions and depreciative behavior (e.g., Keirle and Stephens 2004;Kolasinska et al 2015;Leung and Marion 1996;Pearce-Higgins and Yalden 1997;Wimpey and Marion 2010), this is the first study to empirically demonstrate the positive behavioral feedback loop.…”
Section: Degraded Trail Conditions Promote Off-trail Hiking Behaviormentioning
confidence: 54%
See 3 more Smart Citations
“…This result is logical and was expected given environmental factors (the attributes which describe individuals' immediate surroundings) are consistent and strong predictors of behavioral responses, even when cognitive and sociodemographic characteristics are controlled for (Gifford 2014). While a substantive amount of previous research has either suggested anecdotally or implied a relationship between degraded trail conditions and depreciative behavior (e.g., Keirle and Stephens 2004;Kolasinska et al 2015;Leung and Marion 1996;Pearce-Higgins and Yalden 1997;Wimpey and Marion 2010), this is the first study to empirically demonstrate the positive behavioral feedback loop.…”
Section: Degraded Trail Conditions Promote Off-trail Hiking Behaviormentioning
confidence: 54%
“…Field-based studies (e.g., Kolasinska et al 2015) enable the observation of behaviors under real environmental conditions, but are often limited by high costs and the lack of control over confounding factors such as the presence of others at the recreation setting. On the other hand, laboratory-based studies using experimental designs enable direct control over the factors of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erosion, trampling, littering or vandalism are typical problems reported from many protected areas, not only related to sandstones (particularly many works relating to these problems in Central Europe concern the Tatra Mountains, Pieniny and the Giant Mountains-see e.g. (Buchwał and Fidelus 2008;Hrnčiarová et al 2018;Kasprzak 2005Kasprzak , 2006Kolasińska et al 2015)). Rogowski wrote about these problems in the context of the Table Mountains, referring mainly to the monitoring system of tourist traffic (Rogowski 2017(Rogowski , 2018a(Rogowski , 2018b.…”
Section: Discussionmentioning
confidence: 99%